1994
DOI: 10.1161/01.res.75.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of III-IV linker mutations on human heart Na+ channel inactivation gating.

Abstract: Na+ channel inactivation, a critical determinant of refractoriness, differs in cardiomyocytes and neurons. In rat brain type IIa (rB2a) Na+ channels, a critical residue in the cytoplasmic linker between domains III and IV regulates fast inactivation such that a Phe-->Gln substitution (F1489Q) inhibits inactivation by at least 85%. Since this residue is conserved in voltage-gated Na+ channels, we tested whether F1485Q, the analogous mutation in human heart (hH1a) Na+ channels, has a similar functional effect. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
118
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(133 citation statements)
references
References 31 publications
14
118
1
Order By: Relevance
“…Whole-cell currents recorded from wildtype Na channels expressed in Xenopus oocytes decay rapidly, whereas FQ channels exhibit slower decay and a sizable persistent plateau current at the end of a 100 ms depolarizing pulse to Ϫ 20 mV (Fig. 1 A ), as shown previously (35) for the analogous human cardiac (hH1) Na channel mutant. The half-time of current decay (the interval from the current peak to 50% reduction of the current amplitude) was 5.9 Ϯ 2.3 ms in wild-type channels ( n ϭ 40) vs. 45.9 Ϯ 23.3 ms in FQ channels ( n ϭ 25, P Ͻ 0.0001).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Whole-cell currents recorded from wildtype Na channels expressed in Xenopus oocytes decay rapidly, whereas FQ channels exhibit slower decay and a sizable persistent plateau current at the end of a 100 ms depolarizing pulse to Ϫ 20 mV (Fig. 1 A ), as shown previously (35) for the analogous human cardiac (hH1) Na channel mutant. The half-time of current decay (the interval from the current peak to 50% reduction of the current amplitude) was 5.9 Ϯ 2.3 ms in wild-type channels ( n ϭ 40) vs. 45.9 Ϯ 23.3 ms in FQ channels ( n ϭ 25, P Ͻ 0.0001).…”
Section: Resultssupporting
confidence: 78%
“…Mean open times for FQ single channels were prolonged relative to wild-type (31,35,42), but were still well-described by a single exponential (31,42). Drug association with the open channel at a rate comparable to intrinsic wild-type inactivation should be apparent as a reduction in the mean open time.…”
Section: Resultsmentioning
confidence: 98%
“…The mutation IFM/QQQ in the linker between the third and fourth domains disables inactivation of Na ϩ channels (6,16). IFM/QQQ expressed in human embryonic kidney (HEK)-293 cells has been used to test several clinically relevant Na ϩ channel blockers (6). However, we found that expression of this mutant (especially the persistent portion of I Na ) in HEK-293t cells was poor, which made it difficult to obtain meaningful results.…”
mentioning
confidence: 99%
“…The intracellular linker between domains 3 and 4 is essential for the fast inactivation (i.e., closing) of the Na ϩ channel, and deletion of this region causes persistence of a Na ϩ current (I Na ) during depolarization (2). The mutation IFM/QQQ in the linker between the third and fourth domains disables inactivation of Na ϩ channels (6,16). IFM/QQQ expressed in human embryonic kidney (HEK)-293 cells has been used to test several clinically relevant Na ϩ channel blockers (6).…”
mentioning
confidence: 99%
“…The III-IV linker region that mediates the inactivation process is the most conserved region in various Na + channel isoforms (3,5,20,21,24), while the transmembrane segment S6 of domain IV is important for the resting state block by the local anesthetic etidocaine (11). In the present study, the salicylate-induced enhancement of the tonic block and UDB by quinidine showed voltage dependency but not isoform specificity, indicating that salicylate would increase the binding affinity of quinidine for inactivated Na + channel α subunits through the conserved region of the Na + channel.…”
Section: Effects Of Salicylate On Udb Of Human Namentioning
confidence: 99%